2022
DOI: 10.4178/epih.e2022018
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and stress in Korean general population during the COVID-19 pandemic

Abstract: To investigate the prevalence and risk factors of poor mental health in the general South Korean population during the COVID-19 pandemic MethodsThis cross-sectional, population-based, online survey study was conducted from November 5, 2020 to November 20, 2020 and included adults aged 20-49 years in Chungnam Province, South Korea. A total of 549 adults were included. ResultsA total of 18.8% of the participants had symptoms of depression, 10.6% had symptoms of anxiety, and 5.1% had a high level of perceived str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
3
15
1
2
Order By: Relevance
“…Depression is a leading cause of disability worldwide, and the prevalence of depression in countries around the world has doubled since 2020 18 , 32 . Furthermore, the prevalence of depressive symptoms (PHQ-9 score ≥ 10) in South Korea after COVID-19 pandemic (18.8%) is significantly higher than the rates of 6.1–6.7% reported in previous Korean studies that analyzed population-based data 33 . The increase in the prevalence of depressive symptoms in Korea is larger than the 9.1% increase reported in a US study 34 .…”
Section: Discussioncontrasting
confidence: 57%
“…Depression is a leading cause of disability worldwide, and the prevalence of depression in countries around the world has doubled since 2020 18 , 32 . Furthermore, the prevalence of depressive symptoms (PHQ-9 score ≥ 10) in South Korea after COVID-19 pandemic (18.8%) is significantly higher than the rates of 6.1–6.7% reported in previous Korean studies that analyzed population-based data 33 . The increase in the prevalence of depressive symptoms in Korea is larger than the 9.1% increase reported in a US study 34 .…”
Section: Discussioncontrasting
confidence: 57%
“…Clinical levels of depression, anxiety, or stress were reported by 45% of respondents [ 9 ]. According to another report, 18.8% of the participants had depressive symptoms, 10.6% had anxiety symptoms, and 5.1% had a high level of perceived stress during the COVID-19 pandemic [ 10 ]. A similar increase in distress was observed in a longitudinal community-based prospective cohort study known as the Cardiovascular and Metabolic Etiology Research Center study [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the higher prevalence of depression in women is a finding widely replicated in the literature ( Cortés-Álvarez et al, 2020 ; Ettman et al, 2020 ; Hajek et al, 2022 ; Hernández-Vásquez et al, 2020 ; Yu et al, 2020 ). Similarly, married or cohabiting individuals have also previously been found to have a lower prevalence of CSDS than separated, divorced or never married individuals ( Alzahrani et al, 2022 ; Cortés-Álvarez et al, 2020 ; Ettman et al, 2020 ; Khubchandani et al, 2021 ; Lee et al, 2022 ; Xiong et al, 2020 ; Yu et al, 2020 ). Also, in our data, it was observed that problems with alcohol or drugs (experienced by oneself or by a close person) were associated with higher CSDS; this is fully in line with what is known in the literature ( Pengpid and Peltzer, 2022 ; Tareke et al, 2022 ).…”
Section: Discussionmentioning
confidence: 91%